KEGIATAN MELIPAT ORIGAMI : PENGARUHNYA TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI PAUD AISYAH CEMPAKA SUKAMAJU JONGGOL: (STUDI EKSPERIMEN DI PAUD AISYAH CEMPAKA) - Maripah, Maripah; Pujianti, Yuli (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2023)
The fine motor skills of children aged 5-6 years at the Aisyah Cempaka Sukamaju Jonggol PAUD have not developed as they should, so there needs to be a stimulus to develop these fine motor skills. This study aims to obtain empirical data regarding the significant effect of folding origami activities on the fine motor skills of children aged 5-6 years at PAUD Aisyah Cempaka Sukamaju Jonggol. The research method used in this thesis is a quantitative research method with an experimental type. The experimental method is a research method to look for the effect of certain treatments on others under controlled conditions. The methodology in this study uses a quantitative approach with experimental methods using the Ramdomized Posttest-Only Control Design model. Experiments that use a control group and subjects will be selected randomly or randomly and observed once (post-test). Data collection techniques in this study were carried out through observation and documentation. Based on the results of data collection, it can be concluded that the level of fine motor development of children who were given the treatment of folding origami activities was higher compared to the group of children who were not given the treatment of folding origami activities. This is evidenced by the average post-test result between the experimental group of 51.00 which is higher than the control group of 35.71, with a significant difference of 15.286. The conclusion of this study is that there is a positive and significant effect of folding origami activities on the fine motor skills of children aged 5-6 years at PAUD Aisyah Cempaka Sukamaju Jonggol.